On Improving Capacity and Delay in Multi Tx/Rx Wireless Mesh Networks with Weighted Links - Loo, H.; Soh, Sieteng; Chin, K. (IEEE Press, 2013)
This paper considers the problem of deriving a link schedule for Time Division Multiple Access (TDMA)-based concurrent transmit/receive Wireless Mesh Networks (WMNs) that results in low end-to-end delays as well as high network capacity. We first propose a MAX-CUT heuristic approach, called Algo-2, that maximizes link activations in each slot of a super-frame. Algo-2 is shown to produce better network capacity as compared to existing heuristic approaches and significantly improves the super-frame length of an existing MAX-CUT approach that enforces 2-phase transmit receive restriction – a node that transmits (receives) in slot i ≥ 1 is to become a receiver (transmitter) in slot i + 1. Then, we propose a heuristic solution, called BDA, as a complement to existing schedulers to reduce transmission delays. Since BDA only reorders slots in the super-frame, it maintains each original schedule's super-frame length, and hence capacity, while reducing delays by up to 70% in 6-node random topology networks.